Modern Approaches in Accounting Education: A Literature Review - Yaya Sonjaya; Muh Yamin Noch; Entis Sutisna (Yayasan Vifada Cendikia Indonesia, 2024)
This study explores modern approaches in accounting education, focusing on active learning techniques, technological integration, and soft skills development to better prepare students for professional demands. This study uses a qualitative literature review to analyze academic articles, journals, and books from the last two decades. The literature covers active learning, data analytics, blockchain technology, and essential soft skills in accounting education. The thematic analysis identifies key trends, innovations, and gaps in educational practices. Active learning techniques, such as case-based learning, simulations, and problem-based learning, enhance students' critical thinking, problem-solving, and decision-making skills. Technological integration, especially in data analytics and blockchain, equips students with modern skills. Developing communication, teamwork, and ethical reasoning skills is crucial for success. The study provides actionable recommendations for aligning curricula with professional requirements. This research highlights the transformative potential of modern educational approaches in accounting, emphasizing continuous innovation and adaptation. The comprehensive synthesis offers insights for curriculum development and pedagogical strategies. However, further empirical research, particularly longitudinal studies, is needed to assess the long-term impact of these approaches on graduates' success and to explore diverse educational contexts globally.